Does attending an occasional itinerary music festival drive tourism towards the host city? The case of Eurovision Song Festival - Santos, M-C.; Marques, C. (ATMC 2019 - “MARKETING FOR MORE SUSTAINABLE AND COLLABORATIVE TOURISM”., 2019)
Research show the positive influence of music festivals on host destination tourism, but concern most the local/regular, where exists a tied image between the event and the destination. Furthermore, the findings about the mega-events effect on destinations are mainly from sport events. Does the event brand equity lead attendees to visit the host city? This study contributes to the understanding of the influence of a mega-event on tourism behavior, as it considers a non-permanent/itinerary international music event and explores the emotional - behavioral relation with the event brand equity, the travel motivation and the intention to visit the city. Through foreign visitors who attended the Eurovision 2018, hosted for the first time and unexpectedly in Lisbon, results highlight the partial, direct and indirect, effects of the festival brand equity and the travel motivation on tourism intention. Loyalty towards the event and the interest in visiting the city are important drivers.